Users Incivility and Library Staff Attitudes: Evidence from Khyber Pakhtunkhwa Public Sector University Libraries - Inayat ur Rehman1 , Dr. Rahim Jan & Naveed Ahmed (IJoLIS, 2024)
Purpose: The main purpose of this study was to investigate the association between users' incivility and library staff attitudes. In addition, this study also checked the role of gender in the relationship between users' incivility and library staff attitudes. Design/Methodology/Approach: The data was collected from 57 Library and Information Sciences professionals (LIS) working in Khyber Pakhtunkhwa University academic libraries.